Implementation of green bean waste in the ration on production performance of Padjadjaran laying duck - Emy Saelan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
The green bean waste ration implementation to the quality of duck egg padjadjaran have been done in cage experiment, Faculty of Animal Husbandry Padjadjaran University, Jatinangor, Sumedang-West Java. An exsperiment using laying ducks padjadjaran age 40 weeks as 64 ducks. The research used to Completely Randomized Design (CRD) with 4 treatments and 4 replications of, R0 (100% control rations); R1 (10% green bean waste + 90% control rations); R2 (20% green bean waste + 80% control rations); and R3 (30% green bean waste + 70% control rations); and to see the effect of trend pattern of each treatment was done by orthogonal polynomial test. The results (1) egg production average is R0 (68.45%); R1 (70.84%); R2 (74.40%) and R3 (74.78%) was significantly different (P<0.05) more highly than without control rations;(2) rations of consumption is R0 (154.56 gram); R1 (150.31 gram); R2 (150.18 gram); and R3 (150.60 gram) was significantly different (P<0.05) more highly than without control rations; (3) feed conversion rations is R0 (3.45); R1 (3.44); R2 (3.38); and R3 (3.35) was not significantly different (P>0.05), but significantly different between treatments R0 and R2; R0 and R3 (P<0.05). The use of green bean waste up to 30% in laying ducks rations real increase egg production, improve consumption and feed conversion rations.